Tributação indireta sobre os contratos de softwares: ISSQN, ICMS – mercadorias ou ICMS - comunicação - Barbosa, Jéssyca Verucy Ribeiro (2022)
With technological advances, new forms of digital goods emerged and also the change of existing ones, causing greater complexity in consumer relations. If this disruptive technology was previously sold in physical support, it is now available online with various updates and activities inherent to its operation. Such changes led to the judicialization involving the taxation of the computer program, generating conflicts of jurisdiction between states and municipalities for long years, as prior to occurrences without software, the doubt remained as to whether this good consisted of a service, merchandise, communication services or none of these terms. Thus, in order to assess whether there would be ISSQN or ICMS tax incidence on software commercialization contracts, they were analyzed, from the perspective of Logical-Semantic Constructivism, as definitions of the concepts of "services" and "goods" in the doctrine and in jurisprudence. Furthermore, given the changes in the forms of economic exploitation of software, contracts involving this technology were studied. From this, we can observe that the tax effects varied depending on the transferred rights and the benefits enjoyed under the software contracts